Pendidikan Literasi Meningkatkan Minat Baca Dan Kemampuan Literasi Masyarakat Melalui Kegiatan Belajar Bersama Dan Penyediaan Bahan Bacaan - Dewi, Rani; Suhada, Otong; Nuraeani, Yeni; farhan Syafiq, Herry; Pribadi, Riky (Universitas Majalengka, 2024)
Literacy skills are a crucial foundation for improving the quality of human resources. Literacy is not only defined as the ability to read and write, but also encompasses the ability to understand information, think critically, and utilize knowledge in everyday life. A high level of community literacy will contribute to improving the quality of education, strengthening character, and encouraging sustainable social and economic development. Based on field conditions, community literacy activities are still limited to formal learning activities in schools, while community-based literacy activities such as reading gardens, study groups, or collaborative reading activities have not yet developed optimally. This has resulted in low reading habits in the community and limited opportunities for children to access various sources of knowledge outside the school environment. The objectives of this community service activity are: 1) To increase reading interest among the community, especially children in Panawangan Village; 2) To improve basic literacy skills in the community through collaborative learning activities; 3) To provide and facilitate access to educational and engaging reading materials for the community; 4) To encourage the formation of a learning environment that supports a culture of literacy at the village level; 5) To strengthen the role of the community and village youth in developing sustainable community-based literacy activities.